2022
DOI: 10.1101/2022.07.14.499985
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Adrenal sympathetic nerve mediated the anti-inflammatory effect of electroacupuncture at ST25 acupoint on a rat model of sepsis

Abstract: Acupuncture plays a vital anti-inflammatory action on sepsis through activating autonomic nerve anti-inflammatory pathways, such as sympathoadrenal medullary pathway, but the mechanism remains unclear. This study aims to explore the optimum parameter of electroacupuncture (EA) stimulation in regulating sympathoadrenal medullary pathway and evaluate EA anti-inflammatory effect on sepsis. To explore the optimum parameter of EA at homosegmental acupoint on adrenal sympathetic activity, the left adrenal sympatheti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
(58 reference statements)
0
1
0
Order By: Relevance
“…The sympathetic nervous system plays a dual role in regulating inflammatory responses and mediates both proinflammatory and anti-inflammatory effects. A previous study found that stimulating the homosegmental acupoint ST25 with 3 mA EA can drive the release of peripheral NE from the sympathoadrenal medullary axis ( 108 ). Unlike low-intensity EA, high-intensity EA activates the sympathetic nervous system and inhibits sepsis-induced inflammation.…”
Section: Autonomic Neurobiological Mechanism Of Acupuncture In Inhibi...mentioning
confidence: 99%
“…The sympathetic nervous system plays a dual role in regulating inflammatory responses and mediates both proinflammatory and anti-inflammatory effects. A previous study found that stimulating the homosegmental acupoint ST25 with 3 mA EA can drive the release of peripheral NE from the sympathoadrenal medullary axis ( 108 ). Unlike low-intensity EA, high-intensity EA activates the sympathetic nervous system and inhibits sepsis-induced inflammation.…”
Section: Autonomic Neurobiological Mechanism Of Acupuncture In Inhibi...mentioning
confidence: 99%